The Effect of Flipped Learning Models on Students’ Mathematical Abilities: A Meta-Analysis Study - St. Zulaiha Nurhajarurahmah; Syarifuddin Syarifuddin; Nur Ismiyati (Yayasan Pendidikan Bima Berilmu, 2026)
The Flipped Learning Model (FLM) has become a global phenomenon over the last decade and has significantly influenced educational practices worldwide. However, previous studies have reported inconsistent findings regarding its effectiveness in mathematics learning. Consequently, educators require more reliable and comprehensive evidence concerning the impact of FLM on students’ mathematical abilities. Therefore, this study aims to conduct a meta-analysis to investigate the overall effect of FLM on students’ mathematical abilities and to examine the research characteristics that may influence its effectiveness. This meta-analysis analyzed 36 effect sizes derived from 25 studies published in Scopus-indexed journals between 2014 and 2024. Comprehensive Meta-Analysis (CMA) software was employed to analyze the data. The findings revealed a pooled effect size of 1.35, indicating a very large positive effect of FLM on students’ mathematical abilities. Furthermore, the moderator analysis showed that the effectiveness of FLM varies according to educational level, type of FLM, experimental class capacity, platform type, and type of mathematical ability. These findings suggest that FLM can serve as an effective instructional approach for enhancing students’ mathematical abilities when implemented under appropriate learning conditions.